2022
DOI: 10.1186/s12967-022-03687-y
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine, a gut bacteria metabolite and air pollutant, increases blood pressure and markers of kidney damage including proteinuria and KIM-1 in rats

Abstract: Background Trimethylamine oxide (TMAO) is a biomarker in cardiovascular and renal diseases. TMAO originates from the oxidation of trimethylamine (TMA), a product of gut microbiota and manufacturing industries-derived pollutant, by flavin monooxygenases (FMOs). The effect of chronic exposure to TMA on cardiovascular and renal systems is undetermined. Methods Metabolic, hemodynamic, echocardiographic, biochemical and histopathological evaluations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 76 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…and accumulating in the blood circulation. These toxins and inflammatory mediators have been shown to be involved in the activation of the RAAS system [ 37 ], changes in the tissue microenvironment [ 38 ], and other pathways, which ultimately lead to the burden and damage of the kidney [ 39 ]. It is important to note that this buildup of toxins should result in various organ damage, not just the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…and accumulating in the blood circulation. These toxins and inflammatory mediators have been shown to be involved in the activation of the RAAS system [ 37 ], changes in the tissue microenvironment [ 38 ], and other pathways, which ultimately lead to the burden and damage of the kidney [ 39 ]. It is important to note that this buildup of toxins should result in various organ damage, not just the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Analyte concentrations were evaluated using Waters Acquity Ultra Performance Liquid Chromatography (Waters, Milford, Massachusetts, USA) coupled with Waters TQ-S triple-quadrupole mass spectrometer (Waters, Manchester, UK). Tissue preparation and the exact determination of metabolites in tissue homogenates have been previously described [ 52 ]. The metabolite concentrations in tissues were measured in dry tissue mass.…”
Section: Methodsmentioning
confidence: 99%
“…Although the direct role of TMA and TMAO in the development of hypertension remains uncertain [ 50 ], studies have reported that TMAO might show the ability to prolong the hypertensive effect of angiotensin II [ 51 , 52 ]. It has been noticed in the literature that patients with chronic kidney disease (CKD) demonstrated higher plasma levels of TMAO [ 53 , 54 ].…”
Section: How Does the Microbiota-derived Metabolites Interact With Hy...mentioning
confidence: 99%
“…The recent animal-based study has found that rats receiving TMA solution presented increased arterial blood pressure (especially systolic). Moreover, rats administered a higher dose of TMA showed increased systemic vascular resistance, which might suggest the vasoconstrictive mechanism of observed phenomenon [ 50 , 56 ]. Although TMA and TMAO levels might not play a main role in the pathogenesis of arterial hypertension, they might contribute to the development and progression of the disease [ 57 ].…”
Section: How Does the Microbiota-derived Metabolites Interact With Hy...mentioning
confidence: 99%